Multiple Solutions to Elliptic Equations on RN with Combined Nonlinearities - Miaomiao Yang; Anran Li (Abstract and Applied Analysis)
In this paper, we are concerned with the multiplicity of nontrivial radial solutions for the following elliptic equations (P)λ: -Δu+Vxu=λQxuq-2u+Qxfu,x∈RN; u(x)→0, as x→+∞, where 1<q<2,0<λ∈R,N≥3, V, and Q are radial positive functions, which can be vanishing or coercive at infinity, and f is asymptotically linear at infinity.